Spiritual Care[Givers] Competence in Palliative Care: A Scoping Review - Costeira, Cristina (2024)
To deliver spiritual care, professionals must be skilled in physical, mental, social, and spiritual care. Spiritual care competence includes knowledge, behaviors, attitudes, and skills that enable successful or efficient care. This review aims to identify the scope of competence and the specific skills, knowledge, and attitudes used in providing spiritual care to people needing palliative care, and the main challenges and facilitators. A scoping review was developed using the Joanna Briggs Institute methodology. Six databases (Web of Science; MEDLINE/Pubmed; Scopus; CINAHL; MedicLatina and SciELO) were searched in September 2023, with an update in January 2024. The resulting 30 articles were analyzed using a content analysis approach. Information was categorized into three domains: cognitive, affective, and functional (based on three personal resources: intrapersonal, interpersonal, and transpersonal). Palliative care professionals face a lack of training and insufficient preparation to deliver spiritual care. Spiritual care competence depends on professional spiritual development and experience, spiritual intelligence (cognitive), spiritual humility (affective), and having a critical and reflexive mind (functional). In the future, palliative care should seek to improve competent spiritual care. This review could help clarify the real configuration of competent spiritual care and lead to improvements in a professional’s empowerment when delivering effective spiritual care to patients and families.